2003
DOI: 10.1108/14777830310460432
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of factors influencing waste minimisation and use of recycled materials for the construction of residential buildings

Abstract: Residential building construction activities, whether it is new build, repair or maintenance, consumes a large amount of natural resources. This has a negative impact on the environment in the form depleting natural resources, increasing waste production and pollution. Previous research has identified the benefits of preventing or reducing material waste, mainly in terms of the limited available space for waste disposal, and escalating costs associated with landfills, waste management and disposal and their im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 15 publications
(24 reference statements)
1
36
0
1
Order By: Relevance
“…Notwithstanding existing endeavours to facilitate on-site waste management improvement and set future baselines to help divert waste from landfill, the state of research is strongly dominated by 'end-ofpipe' issues. Indeed, tools, models and techniques have been developed to handle and better manage on-site construction waste segregation (Poon et al, 2001), waste data analysis (Treloar et al, 2003), waste auditing (McGrath, 2001) and reuse (Emmanuel, 2004). At the end of the waste management (Knoeria et al, 2011;Spoerri et al, 2009) and 'hard' technologies (Osmani, 2013) have been developed as a last attempt to divert construction waste from landfill.…”
Section: Construction Wastementioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding existing endeavours to facilitate on-site waste management improvement and set future baselines to help divert waste from landfill, the state of research is strongly dominated by 'end-ofpipe' issues. Indeed, tools, models and techniques have been developed to handle and better manage on-site construction waste segregation (Poon et al, 2001), waste data analysis (Treloar et al, 2003), waste auditing (McGrath, 2001) and reuse (Emmanuel, 2004). At the end of the waste management (Knoeria et al, 2011;Spoerri et al, 2009) and 'hard' technologies (Osmani, 2013) have been developed as a last attempt to divert construction waste from landfill.…”
Section: Construction Wastementioning
confidence: 99%
“…Bossink and Brouwers (1996) attributed design waste causes to errors in contract clauses or incomplete contract documents. Treloar et al (2003) classified origins of construction waste into preconstruction and construction phases. They reported that during the pre-construction phase, waste occurs during planning and designing (e.g.…”
Section: Construction Waste Origins and Causesmentioning
confidence: 99%
“…The site should be selected considering the planned activities such as storing, sorting and processing as well as access by heavy equipment, protection of environmentally sensitive areas and logistical effi ciency. In a disaster situation, it may not be practical to employ a system of waste separation due to amount of debris and time and labor it would require (Treloar et al, 2003;Bekin et al, 2007). According to Selvendran and Mulvey (2005), waste separation system becomes impractical at a post disaster situation as cleanup and recovery became the fi rst priority.…”
Section: Transporting Waste To Relevant Sitesmentioning
confidence: 99%
“…Some of these are already defined in the extant literature including (Mills & Showalter (1999), Pun et al (2006), Begum et al (2006), Treloar et al (2003), Skumatz (2008), Morris et. al.…”
Section: Recurring Cost Versus Income Equationmentioning
confidence: 99%